Impact of first and second eye cataract surgery on physical activity: a prospective study. Issue 3 (20th March 2019) - Meuleners, Lynn B; Feng, Ying Ru; Fraser, Michelle; Brameld, Kate; Chow, Kyle
Abstract : Objectives: To investigate the impact of first eye and second eye cataract surgery on the level of physical activity undertaken by older adults with bilateral cataract. Design: Prospective cohort study. Setting: Three public ophthalmology clinics in Western Australia. Participants: Fifty-five older adults with bilateral cataract aged 55+ years, awaiting first eye cataract surgery. Outcome measures: The primary outcome measure was participation in moderate leisure-time physical activity. The secondary outcomes were participation in walking, gardening and vigorous leisure-time physical activity. Participants completed a researcher-administered questionnaire, containing the Active Australia Survey and visual tests before first eye cataract surgery, after first eye surgery and after second eye surgery. A Generalised Estimating Equation linear regression model was undertaken to analyse the change in moderate leisure-time physical activity participation before first eye surgery, after first eye surgery and after second eye surgery, after accounting for relevant confounders. Results: Participants spent significantly less time per week (20 min) on moderate leisure-time physical activity before first eye cataract surgery compared with after first eye surgery (p=0.04) after accounting for confounders. After second eye cataract surgery, participants spent significantly more time per week (32 min) on moderate physical activity compared with after first eye surgery (p=0.02). There were no significant changes in walking, gardening and vigorous physical activity throughout the cataract surgery process. Conclusion: First and second eye cataract surgery each independently increased participation in moderate leisure-time physical activity. This provides a rationale for timely first and second eye cataract surgery for bilateral cataract patients, even when they have relatively good vision.